2020
DOI: 10.18016/ksutarimdoga.vi.642953
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity, Isolation and Identification of Some Chemical Constituents of Sphaerophysa kotschyana

Abstract: Sphaerophysa kotschyana, an endemic plant belonging to Fabaceae, is distributed around the Tuz Lake in the Konya region. In this study, methanolic extract of S. kotschyana was evaluated for antioxidant capacity. According to obtained data; free radical scavenging capacity (DPPH •) and reducing power activity were observed to be lower than standard antioxidants, cation radical scavenging activity (ABTS •+) was similar to the standard antioxidants. Total phenolic compound was found in leaf-stem and fruit 0.357 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…However, if animals received pinitol during GTT, the MDA content (in relation to the indices of intact animals) decreased by 19.5%, while the activity of SOD and catalase increased by 22.3 and 19.1%, which indicated that pinitol had an antioxidant effect. The work [34] is also of some interest in this regard.…”
Section: D-pinitol (1)mentioning
confidence: 98%
“…However, if animals received pinitol during GTT, the MDA content (in relation to the indices of intact animals) decreased by 19.5%, while the activity of SOD and catalase increased by 22.3 and 19.1%, which indicated that pinitol had an antioxidant effect. The work [34] is also of some interest in this regard.…”
Section: D-pinitol (1)mentioning
confidence: 98%